The Reference to the Leasing of Land on Stela Krakow National Museum MNK-XI-999 from the First Intermediate Period - Demidchik, Arkadiy (Zeitschrift für ägyptische Sprache und Altertumskunde, 2022)
Our knowledge regarding the practice of land lease in Egypt of the III–II millennia BC still remains very patchy. To date, the oldest evidence of its existence are considered to be the Heqanakht letters from the Middle Kingdom. The article argues, however, that oblique references to it occurred as early as in the First Intermediate Period, and simply have not yet been recognized as such. In the autobiographical inscription of the overseer of butchers Merer, the collocation is being shown to be about land lease; Merer’s risk-management strategy against too low inundations was akin to that of Heqanakht. The situation reported in the inscription of the overseer of priests Rehui (Manchester 5052) is reminiscent of that described in the demotic literary story of Djedher (p British Museum EA 69532, ll. 6−9).